Higher Education Opportunity and the Choice of Vocational vs. Academic High School - Chunbing Xing; Yan Sun; Chuliang Luo (Institute of Labor Economics (IZA), 2023)
This research uses CHIP data of 2018 to examine the impact of higher education opportunities on the middle school graduates' choice between academic and vocational high schools. The findings indicate that a higher university quota at the provincial level increases the likelihood of middle school graduates choosing an academic high school, and the probability of choosing a vocational high school is negatively correlated with elite university opportunities in urban China. These results suggest that spatial differences in higher education opportunities significantly influence the type of human capital investment at the high school stage in China.
Keywords: I24; I25; I26; H75; 330; human capital investment; higher education opportunity; the choice of vocational vs. academic high school